Structural Soil in Dense City Areas - Functions and Chances for Urban Greenway Development - Marzena Suchocka; Henryk Kociel (Fábos Conference on Landscape and Greenway Planning, 2016)
The densest parts of cities, parts with the most infrastructure, are losing green areas and trees. The majority of urban site conditions for trees often do not provide them with enough opportunity for healthy growth and development and allow only a few years of vegetation. Visible symptoms of health issues in trees are usually lesions within the crown or stem and are mainly due to the impact of unfavourable factors which have been exerted upon the root system. The most severe causes of poor health in trees are associated with the intense growing environment in urban areas and damaging impact of anthropogenic activities, which affects the properties of the soil environment. Since the 1970s researchers worldwide have been looking for new techniques. During this time are being researched techniques, the application of which would allow the proper development of trees in difficult urban sites, growth comparable to that these trees would experience in their natural habitat. In recent years, throughout Poland there has been an increase in awareness of the high value of trees in urban areas and necessity of using alternative methods of planting to sustain growth. Attempts to solve the problem of short-lived trees in towns and cities have included efforts to provide maximum space for tree rooting along with developing solutions to prevent compaction of the soil. Technology that would potentially provide a solution to both problems may be to use a structural substrate.
Keywords: greenways; structural soil; urban; trees; forestry; soil